Impact of targeted sheep grazing on herbage and holm oak saplings in a silvopastoral wildfire prevention system in south-eastern Spain - Ruiz-Mirazo, Jabier; Robles, Ana Belén (Agroforestry Systems, 2012)
Several wildﬁre prevention programs in southern Europe are currently using livestock grazing for the maintenance of fuelbreaks. This silvopastoral management is valued for being sustainable and effective in reducing fuel loads, but few studies have analyzed other impacts linked to fuelbreak grazing. This paper reports on an experiment performed within the wildﬁre prevention program in Andalusia (southern Spain) with the aim of clarifying and quantifying the effect of fuelbreak grazing on herbage biomass, ground cover, herbage species composition, and growth of holm oak saplings. The study site, located in a semiarid Mediterranean environment, was grazed by a shepherded sheep ﬂock from February to June in three consecutive years at a similar stocking rate. Livestock consumed between 33 and 68 % of herbage production in the different years, and the greatest fuel reduction (remaining dry matter of 200 kg ha -1 ) was registered in Year 2, when rainfall and herbage production was lowest. Ground cover was signiﬁ- cantly affected by grazing: on average, the percentage of bare soil increased three-fold, while herbage cover was reduced by a quarter. The botanical composition of herbage varied remarkably between years, but very little between Grazed and Non-Grazed areas within each year. Non-browsed holm oak saplings became progressively larger than browsed ones, differences only reaching clear statistical signiﬁcance at the end of the three experimental years. At this time, the volume of browsed saplings was 47–56 % smaller than that of non-browsed holm oaks, even though the former had also grown signiﬁcantly in the course of the experiment.
Keywords: biomass; diversity; Grazed fuelbreak; Ground cover; Mediterranean; semiarid